How can the mathematics anxiety rating scale be modified for Indonesian elementary students (aged 10-12)? A psychometric analysis - Solihin, Annas; Mariana, Neni; Purwoko, Budi; Rahmawati, Ika (Journal on Mathematics Education, 2025)
Mathematics anxiety is a well-documented affective factor that negatively influences students’ learning processes and academic achievement. While the Mathematics Anxiety Rating Scale (MARS) is among the most established instruments for assessing this construct, it was originally developed for adolescents and adults, thereby limiting its applicability for younger learners. Despite increasing recognition of the early onset of mathematics anxiety, few validated instruments exist for measuring this phenomenon in elementary school students, particularly within non-Western contexts. Addressing this gap, the present study introduces a culturally and developmentally appropriate adaptation of the MARS for Indonesian elementary students aged 10–12 years. Employing a quantitative psychometric approach with a cross-sectional survey design, data were collected from 324 students via an online questionnaire. The MARS-30 was linguistically simplified and contextually adapted to suit the cognitive and emotional characteristics of younger learners. Exploratory Factor Analysis (EFA) revealed a two-factor solution—Mathematics Test Anxiety and Numerical Anxiety—accounting for 57.62% of the total variance. Confirmatory Factor Analysis (CFA) further supported this structure, yielding satisfactory model fit indices (CFI = 0.94, TLI = 0.92, RMSEA = 0.06, and SRMR = 0.05). Internal consistency reliability was high for the overall scale (α = 0.87) and its subscales (Mathematics Test Anxiety: α = 0.85; Numerical Anxiety: α = 0.84). These results provide robust empirical evidence for the multidimensional nature of mathematics anxiety in children and validate the adapted MARS as a psychometrically sound instrument for use in Indonesian elementary educational settings. The findings underscore the importance of early detection and culturally responsive assessment of mathematics anxiety, informing future research and intervention strategies aimed at mitigating its long-term educational impact.